Investigation of requirements interdependencies in existing techniques of requirements prioritization - Hujainah, Fadhl; Rohani, Abu Bakar; Abdulgabber, Abdullateef (Strojarski Facultet, 2019)
Requirements prioritization (RP) is considered as a key role in producing a successful system by selecting the most important requirements to be released. Requirements interdependencies (RI) is one of the crucial aspects that need to be addressed in RP, since most of the requirements in reality are not independent and have dependencies between each other. Thus, ignoring RI in RP process may lead to produce inaccurate prioritization result which directly impacts the system’s success. In spite of this, little is known about the impact of RI, and obviously further research is urgently required to measure the RI in the RP techniques. Hence, this study aims to investigate and analyze the existence and the execution steps of handling RI in the existing RP techniques to improve the performance of techniques in generating accurate result and assist the researchers and practitioners to select the appropriate technique that can handle RI in prioritization process. The findings indicate that, out of 65 techniques, there are only 4 techniques that handle the RI. The result reveals that these four techniques still suffer from issues of manual process and heavily rely on the experts’ participation. Proposing a new technique is recommended to overcome the identified limitations.